Do what yourself: reevaluation of the value created by online and traditional intermediary. (4th June 2010) - Long, Ju
Information system research posits that online intermediaries could reduce consumer search cost and improve market efficiency, and traditional intermediary would lose market share upon the advent of online intermediary. However, in reality, traditional intermediaries still hold strong market share positions. What are the advantages and disadvantages of online intermediaries and traditional intermediaries? Our research is an effort to address these questions so that we can better explain and predict intermediary's performance. We develop our analysis based on financial intermediation theory, and adopt delegated monitoring model to compare the intrinsic structures and efficiency of online intermediaries and traditional intermediaries. We achieve two important conclusions: first, when information asymmetry exists, traditional intermediary could improve consumer welfare. Second, traditional intermediary improves market welfare because it can diversify its delegated tasks. Based on these results, we also identify market segments and marketing strategies of online and traditional intermediaries.